2011
DOI: 10.1002/ange.201101603
|View full text |Cite
|
Sign up to set email alerts
|

Gold in C‐C‐Kupplungsreaktionen – ein Katalysator so vielseitig wie ein Schweizer Taschenmesser?

Abstract: Die Bildung von C‐C‐Bindungen ist für Organiker der wesentlichste Gesichtspunkt bei der Herstellung von Molekülen. Übergangsmetallkatalysierte Kupplungsreaktionen haben sich zu einem der entscheidenden Instrumente für diese Aufgabe entwickelt. In den letzten Jahren wurde auch Gold als Katalysator für diese Art von Reaktionen entdeckt. Gold als milde carbophile π‐Lewis‐Säure, die zudem in C‐H‐Bindungen inserieren und – wie kürzlich erkannt – Redoxreaktionen eingehen kann, bietet eine ideale Kombination von Eige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(12 citation statements)
references
References 80 publications
0
11
0
1
Order By: Relevance
“…[5] In ähnlicher Weise entwickelten Nevado und Mitarbeiter eine Gold-katalysierte Ethinylierung von "deaktivierten" Arenen mit elektronenarmen Alkinen mit PhI(OAc) 2 als Oxidationsmittel. [6] Zu unserer Überraschung gab es bislang kein Beispiel einer Gold-katalysierten Umsetzung von Propargylestern in Kombination mit PhI(OAc) 2 als Oxidationsmittel.…”
Section: Auunclassified
“…[5] In ähnlicher Weise entwickelten Nevado und Mitarbeiter eine Gold-katalysierte Ethinylierung von "deaktivierten" Arenen mit elektronenarmen Alkinen mit PhI(OAc) 2 als Oxidationsmittel. [6] Zu unserer Überraschung gab es bislang kein Beispiel einer Gold-katalysierten Umsetzung von Propargylestern in Kombination mit PhI(OAc) 2 als Oxidationsmittel.…”
Section: Auunclassified
“…It was found that ethyl, methyl, tert-butyl, benzyl, and allyl acetoacetates (1 a-e) all reacted with 2 a to afford the furans 3 a-e in 55-66 % yields ( Table 2, entries [1][2][3][4][5]. The sterically more hindered 1 f also smoothly underwent the domino reaction (Table 2, entry 6).…”
mentioning
confidence: 98%
“…Despite significant progress, the promising oxidative CÀH/CÀH cross-coupling reactions which obviate the prefunctionalization of both coupling partners have been largely under developed. To the best of our knowledge, only the gold-catalyzed oxidative C(sp 2 ) À H/ C(sp 2 ) À H homocoupling, [6] C(sp 3 ) À H/C(sp 3 ) À H [7] cross-coupling, and C(sp 2 )ÀH/C(sp)ÀH cross-coupling [5] have been realized, and the C(sp 3 )ÀH/C(sp)ÀH cross-coupling still remains unexplored. Following our work in C(sp 3 )ÀH functionalization, [8] we were interested in the gold-catalyzed direct C(sp 3 )ÀH alkynylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Ap romising strategy to expand the scopeo fs uch reactions involves engaging the organogold intermediates in ac ross-coupling process mediated by aA u I /Au III redox cycle. [3] The high potentialo ft he Au I /Au III couple (E 0 =+1.41 V), [4] however, means that stronge xternal oxidants, such as Selectfluor , tBuOOH or hypervalent iodine speciesare generally required.Ensuring high selectivity fort he desired cross-coupled products in these reactions, however,r emainsamajorc hallenge. In most cases, aA u I precatalyst is converted under the reaction [a] A. Tlahuext-Aca,Dr.…”
mentioning
confidence: 99%